Penguatan Tata Kelola Sekolah melalui Implementasi Sistem Informasi Manajemen Terpadu dan Terpantau - Utami Aryanti; Mohamad Taufan Anwar; Irfan Fahriza Fahriza; Nauval Qais Annabil (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
This Community Service activity was motivated by the suboptimal management of academic and administrative data at SMP Negeri 12 Tasikmalaya, which is still carried out separately and partly manually. This condition results in low service efficiency and limited data support for school managerial decision-making. Therefore, the topic of implementing an Integrated and Monitored Management Information System (SIMANTAP) was chosen as a solution to empower schools through the use of information technology. The community service method used was a participatory approach that included partner needs analysis, system design and implementation, user training, and mentoring and evaluation. The results of the activity showed that SIMANTAP was able to integrate academic and administrative data, accelerate service processes, improve information accuracy, and enhance digital literacy among teachers and education personnel. Overall, the implementation of SIMANTAP has made a positive contribution to improving the effectiveness of school governance and supporting digital transformation in the junior high school environment.